Global Challenges in Digital Taxation: Policy, Administration, and Sustainable Development - Cupiadi, Hedi (Indonesian Scientific Publication, 2025)
The rapid expansion of the digital economy challenges traditional tax systems that rely on physical presence. This review synthesizes global regulatory issues of digital taxation and their fiscal implications. OECD initiatives, particularly the BEPS and Two-Pillar Solution, form the basis of reform, though implementation remains uneven. While European states adopt national digital services taxes, countries like India and Indonesia pursue localized strategies. Challenges persist, including limited fiscal capacity, administrative barriers, and legal uncertainties. Despite these obstacles, digital taxation can enhance fiscal sustainability and support development goals. The review emphasizes the need for international cooperation, adaptive policies, and technological innovation. Future research should examine cryptocurrency regulation and links with environmental sustainability.